Intravenous anesthetic propofol suppresses prostaglandin E2 and cysteinyl leukotriene production and reduces edema formation in arachidonic acid-induced ear inflammation. (21st July 2014) - Inada, Takefumi; Hirota, Kiichi; Shingu, Koh
Abstract: Propofol is an intravenous drug widely used for anesthesia and sedation. Previously, propofol was shown to inhibit cyclo-oxygenase (COX) and 5-lipoxygenase (5-LOX) activities. Because these enzyme-inhibiting effects have only been demonstrated in vitro, this study sought to ascertain whether similar effects might also be observed in vivo . In the current studies, effects of propofol were tested in a murine model of arachidonic acid-induced ear inflammation. Specifically, propofol – as a pre-treatment – was intraperitoneally and then topical application of arachidonic acid was performed. After 1 h, tissue biopsies were collected and tested for the presence of edema and for levels of inflammatory mediators. The results indicated that the administration of propofol significantly suppressed ear edema formation, tissue myeloperoxidase activity, and tissue production of both prostaglandin E2 and cysteinyl leukotrienes. From the data, it can be concluded that propofol could exert anti-COX and anti-5-LOX activities in an in vivo model and that these activities in turn could have, at least in part, suppressed arachidonic acid-induced edema formation in the ear.